Private drone companies through a public, private partnership participate in scaling out technologies for better N management. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Drone-companies are using CIMMYT project generated data to assess crop N needs. These companies are providing nutrient recommendations to farmers based on drone-captured NDVI reading which increases NUE by 20% and saves N by 40-70 kg/ha. We feel that public policy that wold provide incentives to drone companies should enhance the adoption of these technology by farmers. The potential area of adoption is ca. 180,000 ha.